2011
DOI: 10.4103/0975-3583.85263
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure profile and left ventricular geometry in Nigerian hypertensives

Abstract: Background:Left ventricular hypertrophy (LVH) is an independent cardiac risk factor in hypertensives and the structural classification of left ventricular (LV) geometry provides additional prognostic information. Ambulatory blood pressure (ABP) monitoring has been shown to be superior to office blood pressure (BP) in relation to hypertension LVH. We investigated ambulatory BP variables in relation to LV geometric patterns in Nigerian hypertensives.Materials and Methods:A total of 130 patients (males = 96, fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Moreover, Ajayi et al reported that the presence of LVH was associated with higher mean ABP and lower percentage nocturnal decline in systolic and diastolic blood pressure. This study confirmed the significance of the non-dipping blood pressure pattern on the development of LVH and its subsequently increased cardiovascular risk [42]. While some studies have reported that LVH is more pronounced in non-dippers, others have found no difference among hypertensive subjects [40,43].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, Ajayi et al reported that the presence of LVH was associated with higher mean ABP and lower percentage nocturnal decline in systolic and diastolic blood pressure. This study confirmed the significance of the non-dipping blood pressure pattern on the development of LVH and its subsequently increased cardiovascular risk [42]. While some studies have reported that LVH is more pronounced in non-dippers, others have found no difference among hypertensive subjects [40,43].…”
Section: Discussionsupporting
confidence: 84%
“…Upper normal limits for LV mass index were 134 and 110 g/m 2 in men and women respectively. 13 , 17 Relative wall thickness (2 × posterior wall thickness/LV diastolic diameter) was calculated. A partition value of 0.45 for relative wall thickness was used for men and women.…”
Section: Methodsmentioning
confidence: 99%
“…In Nigeria, studies on LV geometric patterns 10 13 involving large number of hypertensive patients are limited and there is little information regarding the association between age and geometric patterns in hypertensive Nigerians. We therefore present an eight-year echocardiographic study of LV geometric patterns of 1020 consecutive hypertensive patients seen at the Cardiac Care Unit of Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC) Ile-Ife, a tertiary hospital in Southwest Nigeria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morabito et al in 2016 explored the use of deep machine learning using CNN among Alzheimer Disease and normal candidates and was able to classify mild cognitive impairment which is a feature of early dementia. They averaged a classification accuracy of 82% [12].…”
Section: Various Studies Of Applications Of Anns On Classification Ofmentioning
confidence: 99%